Perbedaan Tingkat Prestasi Belajar antara Siswa yang Mengalami dan Tidak Mengalami Adiksi Internet di SMA Negeri 1 Salatiga - Nugraheni, Sayekti Asih; ., Machmuroch; Hikmayani, Nur Hafidha (Nexus Pendidikan Kedokteran dan Kesehatan, 2012)
Background: Internet addiction is potentially experienced by young people, including students. Students with internet addiction may suffer from lack of sleep, fatigue, decreased performance on social activity, anxiety, and apathy. Furthermore, internet addiction may cause negative effects on studentsâ achievement level. This study aims to examine the difference of learning achievement level between students of SMA Negeri 1 Salatiga who were addicted and not addicted to the internet. Methods: This was an analytical observational research using cross-sectional approach, conducted from May to July 2012 at SMA Negeri 1 Salatiga. Subjects were 11th grade students majoring science who were sampled using simple random sampling method. Eighty subjects were asked to fill out the Youngs Diagnostic Questionnaire (YDQ) and the Lie Scale of the Minnesota Multiphasic Personality Inventory (L-MMPI), both were Bahasa Indonesia versions. Status of having internet addiction was identified from the YDQ scores, while learning achievement level was determined from studentsâ average scores at the first and second semester. Data were analyzed using independent t test, Ï2 test, and prevalence ratio (PR). Results: Seventeen students (21,25%) were found to be addicted to internet, 11 (64,7%) of which showed poor learning achievement. Statistical analysis showed a significant difference of studentsâ scores between those having and not having internet addiction (82,99 versus 84,72; t = -3,792; p < 0.001). The learning achievement levels also differed significantly between the two groups (Ï2 = 6,128; p = 0,013), where poor achievement level was found two times higher in group of students having internet addiction (PR = 2,04). Conclusions: There was a significant difference of learning achievement level between students having and not having internet addiction at SMA Negeri 1 Salatiga. Keywords: Internet addiction, learning achievement level